TINJAUAN HUKUM ISLAM TERHADAP TRADISI PRAKTIK NELON LAHAN PERTANIAN DI DESA GELAP KECAMATAN LAREN KABUPATEN LAMONGAN - Muhammad Arif Saifuddin (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
This study resulted in that tradition melon practices of agricultural land in the village of Laren Dark District of Lamongan. First, the formation of the contract agreement nelon agricultural land is only made orally by using the principle of mutual trust. Second, plant seeds derived from the manager to the provisions period based on the growing season. Third, the distribution of the results is done after harvest with a percentage of 1/3 to 2/3 to land owners and tenants. Fourth, the distribution of proceeds to the land owners in the initial contract dipanjari time of the agreement. Fifth, if the land does not produce anything or failed harvests, the only loss is borne by the tenant for loss that was not caused by a natural disaster. From these results we can conclude, that tradition nelon practices of agricultural land in the village of Laren Dark Lamongan District of permissible under Islamic law, but when the plant seedlings from tenants there that allow some scholars and some do not allow. Similarly, in the distribution of the results the percentage of 1/3 and 2/3 for the owner of the land to the tiller was legitimate in the mukabarah, and it is in accordance with the opinion of scholars and clerics Shafi'ites H{anabilah. Then, the results for the division of the land owners dipanjari at the beginning of the contract when the agreement was also valid in the muka>barah, while the percentage distribution of the result is determined at the beginning of the current contract agreement and the division of the results done after harvest or after calculating the pros and cons in mind.